Water usage pattern in the aftermath of COVID-19 - Venu Prasad H D; Naveena K (Environment Conservation Journal, 2022)
Maintenance of good health and avoiding a viral infection is the prime focus for an individual during COVID-19 pandemic. Water being a universal solvent is used widely to clean the disinfectants in public places and individual household level. This study was designed to find any change in the water consumption pattern among the households after the emergence of COVID-19. To study this, a questionnaire was prepared and sent to the respondents through Google Forms. Collected data was analysed using suitable statistical methods and the results indicate that there was a significant change in the consumption pattern of drinking water from cold to hot (37.98%) among the respondents and also with respect to the total water usage. As the disease is communicable in nature, more water is needed to clean and disinfect the surface areas, washing hands etc. This eventually has a significant burden on the water resources in countries where water is already deficient, like India. It is recommended to adopt water conservation practices/technologies at the individual level by means of rain water harvesting techniques or use of efficient water aerator taps etc. to reduce water consumption.